2017
DOI: 10.3389/fphar.2017.00211
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Compatibility Effects of Huangqin Decoction on the Treatment of Irinotecan-Induced Gastrointestinal Toxicity Using Untargeted Metabolomics

Abstract: Huangqin decoction (HQD), a traditional Chinese medicine (TCM), has been widely used to treat gastrointestinal syndrome in China for thousands of years. Chemotherapy drug irinotecan (CPT-11) is used clinically to treat various kinds of cancers but limited by its side effects, especially delayed diarrhea. Nowadays, HQD has been proved to be effective in attenuating the intestinal toxicity induced by CPT-11. HQD consists of four medicinal herbs including Scutellaria baicalensis Georgi, Glycyrrhiza uralensis Fisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Although a large number of clinical drugs, such as loperamide vhydrochloride, cholestyramine, and levofloxacin, have been regarded as the promising options for the prevention of delayed diarrhea caused by CPT‐11, the improper mechanism and dosage are common causes for treatment failure (X. Wang et al, ). Moreover, herbal medicine PHY906 has been reported to attenuate the intestinal toxicity induced by CPT‐11 (Cui et al, ; Lam et al, ). PHY906 is composed of four main herbs of which baicalin, a β‐glucuronidase inhibitor, is the most abundant ingredient (Kummar et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large number of clinical drugs, such as loperamide vhydrochloride, cholestyramine, and levofloxacin, have been regarded as the promising options for the prevention of delayed diarrhea caused by CPT‐11, the improper mechanism and dosage are common causes for treatment failure (X. Wang et al, ). Moreover, herbal medicine PHY906 has been reported to attenuate the intestinal toxicity induced by CPT‐11 (Cui et al, ; Lam et al, ). PHY906 is composed of four main herbs of which baicalin, a β‐glucuronidase inhibitor, is the most abundant ingredient (Kummar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Various traditional herbal medicines, such as PHY906 (Cui et al, ; Lam et al, ) and saireito (Fujita et al, ), have been reported to attenuate the intestinal toxicity induced by CPT‐11 or 5‐fluorouracil; however, the active ingredient and attenuation mechanism were not identified in those studies. Additionally, flutamide, a nonsteroidal antiandrogen used primarily to treat prostate cancer, is also hydrolyzed by hCE2 to FLU‐1, which can be further metabolized to N‐hydroxy FLU‐1 by human CYP3A4 (Aizawa et al, ; Kobayashi, Fukami, Shimizu, Nakajima, & Yokoi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea is categorized into four types based on its mechanism of action: Osmotic diarrhea, secretory diarrhea, inflammatory and infectious diarrhea, and diarrhea related to motility disorders. Clinically, diarrhea-predominant irritable bowel syndrome and functional diarrhea are associated with alterations in intestinal motility; therefore, some anti-diarrheal agents decreasing intestinal transit, such as opioids and 5-HT 3 antagonist, have been used to manage these diseases (1).…”
Section: Introductionmentioning
confidence: 99%
“…Scutellaria baicalensis is widely used as a herbal medicine in East Asia and Europe for gastrointestinal tract (GI) disorders including dysentery, diarrhea, and abdominal pain (2). Experimentally, it has anti-diarrheal effect on irrinotecan-induced diarrhea in rats (3). Clinically, it demonstrated an improvement in the diarrhea toxicity grade and reduction of frequency of severe diarrhea in lung cancer patients with irrinotecan-induced diarrhea (4).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our recent metabolomics study on peiminine, a compound extracted from the bulbs of Fritillaria thunbergii which has been traditionally used in TCM, demonstrated inhibitory effect on CRC cell proliferation by inducing apoptosis and autophagy and modulating key metabolic pathways [14]. In addition, Cui et al [18] recently reported using LC-MS- and GC-MS-based untargeted metabolomics strategy to quantitatively evaluate the effects of Huangqin decoction on irinotecan-induced gastrointestinal toxicity, suggesting a potential application of metabolomics analysis in elucidating the comprehensive mechanisms of action of TCMs or combinations of medications.…”
Section: Introductionmentioning
confidence: 99%